2007
DOI: 10.1158/1055-9965.epi-07-0581
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Dietary Acrylamide Intake and the Risk of Endometrial, Ovarian, and Breast Cancer

Abstract: Background: Acrylamide, a probable human carcinogen, was detected in various heat-treated carbohydrate-rich foods in 2002. The few epidemiologic studies done thus far have not shown a relationship with cancer. Our aim was to investigate the association between acrylamide intake and endometrial, ovarian, and breast cancer risk. Methods: The Netherlands Cohort Study on diet and cancer includes 62,573 women, aged 55-69 years. At baseline (1986), a random subcohort of 2,589 women was selected using a case cohort a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
187
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(201 citation statements)
references
References 42 publications
8
187
3
3
Order By: Relevance
“…If acrylamide were to affect these systems, it may primarily be a risk factor for ER and PR positive breast cancer, as reproduction-related exposures seem to be more strongly associated with the risk of receptor-positive breast cancer [3]. In a previous analysis, we observed no association with overall breast cancer risk [9]. Here, we aim to investigate the association between dietary acrylamide intake and postmenopausal breast cancer risk in receptor-defined subgroups in a large prospective cohort study.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…If acrylamide were to affect these systems, it may primarily be a risk factor for ER and PR positive breast cancer, as reproduction-related exposures seem to be more strongly associated with the risk of receptor-positive breast cancer [3]. In a previous analysis, we observed no association with overall breast cancer risk [9]. Here, we aim to investigate the association between dietary acrylamide intake and postmenopausal breast cancer risk in receptor-defined subgroups in a large prospective cohort study.…”
Section: Introductionmentioning
confidence: 76%
“…This mechanism has been the focus of most of the toxicological acrylamide research. Recently, some, but not all, epidemiological studies found a positive association between dietary acrylamide exposure and the risk of strongly endocrinerelated cancers (ovarian, endometrial, and ER positive breast cancer) [8,9], which may suggest a different carcinogenic pathway. One of the hypothesized mechanisms behind acrylamide-induced carcinogenicity, other than genotoxicity, is modulation of sex hormone systems [10].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolite of acrylamide, glycidamide, can form adducts with haemoglobin and DNA. Several large scale epidemiological studies have reported no link between dietary acrylamide and cancer, but one prospective study has reported a link between dietary acrylamide intake and endometrial and ovarian cancer (but not breast cancer) in postmenopausal women (Hogervorst et al 2007). …”
Section: Acrylamidementioning
confidence: 99%
“…When acrylamide levels were lower than the quantification limit, a value half of the quantification limit was assigned because they may still contain some acrylamide. However, dairy products and cereals, potatoes, meat, fish, and vegetables when boiled or raw were assigned values of zero, following previous studies (31,32). As the acrylamide concentration of steamed white rice was reported to be less than 0.5 ng/g, this was also regarded to be a value of zero.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed description of the food-frequency questionnaire, its reliability, and validity for calculating nutrient intakes has been published previously (33). Although the validity of the values for acrylamide intake could not be directly tested, we examined correlations between the questionnaire and 12 daily diet records kept over a 1-year period for the major food sources of acrylamide, like other studies (31,32); the Spearman correlation coefficients were 0.49 for potatoes, 0.57 for coffee, 0.62 for meats and meat products, and 0.49 for vegetables.…”
Section: Methodsmentioning
confidence: 99%